Marine cadastre issue and conceptual for implementation in Malaysia / Ashraf Abdullah, Zakaria Mat Arof and Jamil Tajam - Abdullah, Ashraf; Mat Arof, Zakaria; Tajam, Jamil (Universiti Teknologi MARA, Perlis, 2013)
In Malaysia, there are various activities in marine environment such as fishing, heritage area, aquaculture, tourism attraction, oil and gas exploration and Marine Park itself, which requires proper administration and management. The United Nations Convention on the Law of the Sea (UNCLOS) institute a comprehensive jurisdictional regime where Malaysia can claim, manage and utilize its maritime territories (United Nations, 1983). The law and regulations for a marine area is indistinct till today despite the implementation of Marine Spatial Planning for administrating and managing. This is due to the issue on the boundary description which is vague, inaccurate, or incorrectly presented on a map. Therefore, effective regulations dealing with marine spatial issue are yet to fully implement in marine organizations and administration. Serious actions need to be taken in adopting a new mechanism for successful management. This paper aims to examine marine legal in Malaysia from the context of marine spatial, investigates its procedure and data besides providing some inputs for marine legal draft in Malaysian marine cadastre scope. The methodology used in this study includes direct interview and discussion on legal issues associated with marine rights. Conflict of area in marine institutional governance at Langkawi Island is used as the study case. Finally, this research is expected to develop a marine cadastre model and conceptual as proposed in the official guideline for particulars agency especially to marine institutions in Malaysia.